Capability of biodentine and the mineral trioxide aggregate mta sealing in furcal perforation repair. Literature review - Silvana Benavides; Alejandra Guallo; Yecenia Carrillo (Kiru)
Endodontic therapy seeks to maintain natural dentition's integrity in form function and aesthetics. Accidents during these procedures commonly occur which affect the prognosis of root canal treatment. A furcal perforation is a complication that refers to the mechanical or pathological communication between the pulp chamber and supporting ligament, in the lower area of the pulp chamber and leads to the worst result of the treatment. It can occur during the endodontic access or during the preparation of an intraradicular retainer, although it can also be due to caries lesions of root absorption. For long term success, perforations should be repaired as soon as possible with a biocompatible material any delay causes bacterial contamination and leads to complicated periodontal endodontic lesions. An ideal perforation repair material , should create an adequate seal, be biocompatible, not be affect by blood contamination, be a bactericide, radiopaque, induce bone formation and healing, induce mineralization, cementogenesis, facilite its manipulation and application. Various materials have been used to repair furcal perforations including MTA and Biodentine. The objective of this study is to carry out a review of the literature about the sealing capacity of MTA and Biodentine in the repair of furcal perforations. To reach this objective a bibliographic review is carried out in the leading odontological databases and magazines and articles are chosen according to their scientific validity their relationship with the topic and the year of publication wich stretches from 2009 to 2018.